2017
DOI: 10.3233/nre-001481
|View full text |Cite
|
Sign up to set email alerts
|

Stroke and sexual functioning: A literature review

Abstract: Sexual rehabilitation needs to be an integrative part of stroke patients' rehabilitation process, preferably at the interdisciplinary level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 62 publications
2
21
0
2
Order By: Relevance
“…Importantly, more than threequarters of HCPs in this study reported having little or no knowledge about working with sexual health after stroke. Similar findings have been reported by others (8,17,20,21) as one of the major barriers to provide information about sexuality to patients and their partners. Most HCPs expressed a need for knowledge within several areas of sexual medicine/ sexology and preferred an interdisciplinary model for sexological education and training.…”
Section: Perceived Low Level Of Knowledge: a Barrier To Be Overcomesupporting
confidence: 90%
See 3 more Smart Citations
“…Importantly, more than threequarters of HCPs in this study reported having little or no knowledge about working with sexual health after stroke. Similar findings have been reported by others (8,17,20,21) as one of the major barriers to provide information about sexuality to patients and their partners. Most HCPs expressed a need for knowledge within several areas of sexual medicine/ sexology and preferred an interdisciplinary model for sexological education and training.…”
Section: Perceived Low Level Of Knowledge: a Barrier To Be Overcomesupporting
confidence: 90%
“…HCPs' age and gender were not found to be associa ted with level of comfort addressing sexuality, while those reporting a higher level of knowledge were more likely to feel comfortable. This confirmed previous studies describing knowledge as an important factor for being comfortable (8,21). Being employed at centres scoring high on sexual health policy was also asso ciated with being comfortable addressing sexuality.…”
Section: Perceived Low Level Of Comfort: a Multifactorial Barriersupporting
confidence: 88%
See 2 more Smart Citations
“…22 Prevalence of sexual complaints in the present study was among the highest reported compared to previous findings on sexuality after stroke. [12][13][14] Experiencing manifest sexual complaints is more likely to cause ongoing distress than those occurring occasionally, 44 explaining the strong association to sexual dissatisfaction. In gender-specific analyses, only sexual complaints perceived as distressing turned out to be significant for sexual satisfactions in both women and men.…”
Section: Discussionmentioning
confidence: 99%